The Influence of Debt to Asset Ratio (DAR), Earning Per Share (EPS), Current Ratio (CR) on Sector Sharia Stock Prices Industry Goods Consumption (in Companies Listed on the Sharia Stock Index (ISSI) - Kumalasari, Listia; Falahuddin, Falahuddin (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to provide empirical evidence regarding the influence of financial performance on stock prices. The ratios used are Debt To Asset Ratio (DAR), Earning Per Share (EPS), and Current Ratio (CR) in consumer goods industry companies listed on the Indonesian Sharia Stock Index (ISSI) for 2020-2022. The population in this study was 57 companies. The sampling technique used purposive sampling to obtain 45 company samples with 135 observations. This research is quantitative research using secondary data collected using documentation and literature study techniques obtained via www.idx.co.id or the respective company's official website which is analyzed using panel data analysis. The results of this research show that the Debt To Asset Ratio (DAR) variable has no significant effect on Sharia stock prices, the Earning Per Share (EPS) variable has no significant effect on Sharia stock prices, and the Current Ratio (CR) variable has a significant effect on Sharia stock prices.